2020
DOI: 10.3390/toxins13010003
|View full text |Cite
|
Sign up to set email alerts
|

Crouching Tiger, Hidden Protein: Searching for Insecticidal Toxins in Venom of the Red Tiger Assassin Bug (Havinthus rufovarius)

Abstract: Assassin bugs are venomous insects that prey on other arthropods. Their venom has lethal, paralytic, and liquifying effects when injected into prey, but the toxins responsible for these effects are unknown. To identify bioactive assassin bug toxins, venom was harvested from the red tiger assassin bug (Havinthus rufovarius), an Australian species whose venom has not previously been characterised. The venom was fractionated using reversed-phase high-performance liquid chromatography, and four fractions were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…−50% in less than a minute, probably representing the effects of fast-acting compounds such as neurotoxins. Venom peptides from assassin bugs that have been suggested to act as neurotoxins include ptu1like peptides, cystatins, and CUB domain proteins [16,30]. The fast decrease in [Ca 2+ ] i was followed by a gradual increase over several minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…−50% in less than a minute, probably representing the effects of fast-acting compounds such as neurotoxins. Venom peptides from assassin bugs that have been suggested to act as neurotoxins include ptu1like peptides, cystatins, and CUB domain proteins [16,30]. The fast decrease in [Ca 2+ ] i was followed by a gradual increase over several minutes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study attempted to identify the insecticidal venom components of the red tiger assassin bug Havinthus rufovarius (Bergroth) by determining the toxic activity of venom fractions. The fractions with the strongest paralytic and lethal effects on sheep blowflies contained primarily a CUB domain protein and a cystatin, suggesting that one or both proteins contribute to the venom's insecticidal activity [16]. In the hematophagous bug Triatoma infestans (Klug), trialysin has been identified as a major toxic component that exerts cytotoxic effects against bacteria, protozoa, and mammalian cells by disrupting cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of compounds in the salivary venom of predatory heteropterans is essential for assessing their potential for biological pest management. Recently, with the development of transcriptome and proteome analyses, the composition of predatory heteropteran venoms has been studied in several species, including assassin bugs (the family Reduviidae) [8,9], minute pirate bugs (the family Anthocoridae) [10], and true water bugs (the infraorder Nepomorpha) [11,12] (Figure S1). These studies revealed that venoms are typically complex cocktails of organic and inorganic compounds, with numerous proteinaceous components [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The saliva of predatory bugs has been identified as a source of toxins, including some digestive enzymes, proteins, peptides, etc. ( Beak and Lee, 2014 ), which have the functions of paralyzing prey, defense, digesting nutrients, antibacterial, and lysing cells ( Walker et al, 2016 ; Tonk et al, 2020 ; Wait et al, 2020 ). Currently, the research on the application of predatory bug venom mainly focuses on the Reduviidae bugs.…”
Section: Introductionmentioning
confidence: 99%
“…The venom of Pristhesancus plagipennis was injected into Lucilia cuprina , and paralysis and death could be produced after 15 min of application, while injection into crickets could immediately produce paralysis ( Walker et al, 2018a ). Four components isolated from the salivary glands of Havinthus rufovarius were injected into L. cuprina , resulting in paralysis and death ( Wait et al, 2020 ). Previously, our laboratory found that the salivary gland secretion of E. furcellata had a lethal effect on the fourth instar larvae of Spodoptera litura and affected its detoxification enzyme activity.…”
Section: Introductionmentioning
confidence: 99%